Accuracy and Reliability of YouTube Videos as an Information Source for Osteoporosis - Ali Çağdaş Yörükoğlu; Süleyman Utku Uzun (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Objectives:There is a little data available in the literature investigating videos related to osteoporosis in the internet media. The present study investigates the characteristics and scientific accuracy of the videos related to osteoporosis, which have been uploaded and broadcast on the YouTube website.Materials and Methods:The key word “osteoporosis” was searched in February 2016 on the YouTube browser without any filters. The contents of the recruited videos were assigned to three groups, including general information, preventing the disease, and treatment; while their usefulness was classified as useful, moderately useful and not useful.Results:Two hundred and thirty-seven (47.4%) videos formed the study group. Sixty-four point one percent of these videos contained definitive and diagnostic information about the disease, and 87% included preventative suggestions. It was noted that 56.9% of the videos had content related to treatment. Regardless of uploaders, the videos about osteoporosis were found to be low scores but when the videos were grouped according to uploaders; the videos, which were uploaded by the governmental and official institutions or associations had the highest diagnostic, preventing and treatment scores.Conclusion:It cannot be proclaimed that the videos, which are related to osteoporosis, inform people accurately enough. It seems crucial that videos giving information about health on such websites as YouTube, should be controlled beforehand or that more public viewing of videos uploaded by the governmental and official institutions should be ensured. Considering the large volume of information gathering from this type of internet source, by arranging the necessary regulations, video sharing websites may become more useful in public education.